2016
DOI: 10.1111/joor.12397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of occlusal vertical dimension on swallowing patterns and perioral electromyographic activity

Abstract: Abnormal swallow patterns have been associated with specific dentofacial traits, such as an anterior open bite, but the cause-effect relationship between swallowing and malocclusion remains highly controversial. The aim of this research was to determine the effects of acute change in occlusal vertical dimension (OVD) on intraoral pressure swallow patterns and perioral electromyographic activity (EMG) during swallowing. Ten volunteers (five female, five male; 27-32 years) repeated standardised swallowing tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…Atypical swallowing develops as a compensatory movement pattern when normal movement is inhibited in some way. A tongue thrust swallow involves excessive perioral effort and the tongue exerts forward and/or lateral pressure into the teeth, rather than vertical pressure into the hard palate with a front to back motion . Lingual‐palatal stabilization for the swallow is far weaker in children with PCB .…”
Section: Impact Of Swallowingmentioning
confidence: 99%
See 1 more Smart Citation
“…Atypical swallowing develops as a compensatory movement pattern when normal movement is inhibited in some way. A tongue thrust swallow involves excessive perioral effort and the tongue exerts forward and/or lateral pressure into the teeth, rather than vertical pressure into the hard palate with a front to back motion . Lingual‐palatal stabilization for the swallow is far weaker in children with PCB .…”
Section: Impact Of Swallowingmentioning
confidence: 99%
“…A tongue thrust swallow involves excessive perioral effort and the tongue exerts forward and/or lateral pressure into the teeth, rather than vertical pressure into the hard palate with a front to back motion. 39 Lingualpalatal stabilization for the swallow is far weaker in children with PCB. 40 This swallowing pattern reinforces a low resting posture, contributing to HNP, PCB and further malocclusion.…”
Section: Impac T Of Swallowingmentioning
confidence: 99%
“…Various studies have reported on tongue dynamics during swallowing in patients with anterior open bite or in a state simulating anterior open bite on experimental occlusal elevation . Of these methods, electropalatography and measurement of tongue pressure have been widely used to evaluate tongue dynamics during swallowing, because tongue pressure has been identified as one cause of malocclusion .…”
Section: Introductionmentioning
confidence: 99%
“…Of these methods, electropalatography and measurement of tongue pressure have been widely used to evaluate tongue dynamics during swallowing, because tongue pressure has been identified as one cause of malocclusion . However, complex appliances need to be manufactured for each patient, and an acclimation period is required after fitting of the appliance, meaning that there has been no suitable method of easily obtaining a large volume of data in routine clinical practice thus far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation